Neutrophil gene expression patterns in multiple trauma patients indicate distinct clinical outcomes - Bogner-Flatz, Viktoria; Braunstein, Mareen; Bazarian, Jeffrey J.; Keil, Leonard; Richter, Peter H.; Kusmenkov, Thomas; Biberthaler, Peter; Giese, Thomas (Journal of surgical research, 2022)
Introduction - Patients after polytrauma suffer from posttraumatic immune system dysregulation and multiple organ dysfunction. Genome-wide microarray profiling in monocytes revealed a regulatory network of inflammatory markers around the transcription factor AP-1 in severely injured patients. Recent research focuses on the role of neutrophils in posttraumatic inflammation. The aim of this study was, therefore, to evaluate the impact of this inflammatory network in neutrophils. - Materials and methods - Blood sampling and neutrophil separation were performed on admission of the patient and at 6 h, 12 h, 24 h, 48 h, and 72 h after trauma. Neutrophil expression levels of the target genes c-Jun, c-Fos, BCL2A, MMP-9, TIMP-1, ETS-2, IL-1β, and MIP-1β were quantified by RT-qPCR. Patients were assorted into groups according to distinct clinical parameters like massive transfusion (>10 RBC units/24 h), injury severity (ISS), 90-d survival, and the presence of traumatic brain injury (defined by ICI on head CT). Statistics were calculated by Mann-Whitney Rank-Sum Test, Receiver Operating Curves, and binary multiple logistic regression. - Results - Forty severely injured patients (mean ISS 36 ± 14) were included. BCL2A, MMP-9, TIMP-1, and ETS2 levels showed a significant correlation to 90-d-survival in the early posttraumatic period (6 h-24 h). Furthermore, differential BCL2A, IL-1β, MIP-1β, and MMP-9 regulation was observed in patients requiring massive transfusion. We could further show a significant TIMP-1 response in trauma PMN associated with traumatic brain injury. - Conclusions - This study of seriously injured patients highlights very early posttraumatic transcriptional changes in PMNs, which were clearly associated with posttraumatic events and outcomes.
Gesehen am 24.08.2022